The advanced grammar book - Steer, Jocelyn (Heinle & Heinle publishers, 1998)
This best-seller presents grammatical structures through sophisticated and up-to-date contexts. The wide range of communicative activities, newly simplified charts, and an expanded writing section lead students from grammar recognition to production.